Analysis of radar signals by PSD methods - Rejfek, Luboš; Beran, Ladislav; Chmelař, Pavel; Chmelařová, Natalija; Pek, Viktor; Fišer, Ondřej (Institute of Advanced Science Extension, 2016)
The article is targeted on an application of selected Power Spectral Density (PSD) methods to analyze the rador signals with frequency modulated pulses. First, simulated signals to test the power spectral density methods themselves are used. The second step was the test of the methods applied on real measurement. The primary aim of the work was to focus on the analysis of the long targets by parametric power spectral density methods. The involved methods are Periodogram, Multiple Signal Classification (MUSIC) method and Eigen value method
Analýza radarových signálů pomocí PSD metod
Keywords: Pulse Radar With Frequency Modulated; Pulses; PSD; Multi Signal Classification Method